Pengaruh Pengawasan Terhadap Produktivitas Kerja Pada PT. Power Seal Technology Singapore Region Sumatera - Benny Usman (Universitas PGRI Palembang, 2019)
ABSTRACT The purpose of this study is to determine whether there is an influence of supervision on the work productivity of PT. Power Seal Technology Sumatra Region. The population in this study were all production staff at PT. Power Seal Technology Sumatra Region totaling 163 people. While the sample studied from 20% of the number of employees is 32 people.From a simple linear regression equation Y = a + bX so the equation is Y '= 19,215 + 0,506X where the value of a = 19,215 and the value of b = 0,506 towards the ups and downs of work productivity. The results of the calculation of the correlation coefficient analysis R2 = 0.6192 = 0.383. This can be interpreted that the supervision variable has an effect on work productivity of 38.3% while the remaining 61.7% (100% - 38.3%). And for the hypothesis test the value of tcount = 4.315 is greater than t table = 1.697 (see attachment table t) at the real level of 0.05, for dk = n - 2 = 32 - 2 = 30. Thus the value of tcount is greater than the value of ttable (4,315> 1,697) then the decision is rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha) means that there is an influence between supervision of employee productivity in the production field of PT. Power Seal Technology Sumatra Region. Keywords: Supervision, Work Productivity.ABSTRAK Tujuan penelitian ini adalah untuk mengetahui apakah ada pengaruh pengawasan terhadap produktivitas kerja PT. Power Seal Technology Region Sumatera.Populasi dalam penelitian ini adalah seluruh pegawai bidang produksi padaPT. Power Seal Technology Region Sumaterayang berjumlah 163 orang. Sedangkan sampel yang diteliti dari 20% jumlah pegawai adalah 32 orang. Dari persamaan regresi linier sederhana Y = a + bX sehingga persamaannya adalah Y' = 19,215 + 0,506X dimana nilai a = 19,215 dan nilai b = 0,506 terhadap naik turunnya produktivitas kerja.Hasil perhitungan analisis koefisien korelasi R2 = 0,6192 = 0,383. Hal ini dapat diartikan bahwa variabel pengawasan berpengaruh terhadap produktivitas kerja sebesar 38,3% sedangkan sisanya 61,7% (100% – 38,3%).Dan untuk uji hipotesis nilai thitung = 4,315 lebih besar dibandingkan dengan ttabel = 1,697 (lihat lampiran tabel t) pada taraf nyata 0,05, untukdk = n - 2 = 32 - 2 = 30. Dengan demikian nilai thitung lebih besar dari nilai ttabel (4,315> 1,697) maka keputusannya adalah menolak hipotesis nol (Ho) dan menerima hipotesis alternatif (Ha) berarti ada pengaruh antara pengawasan terhadap produktivitas pegawai pada bidang produksi PT. Power Seal Technology Region Sumatera. Kata Kunci : Pengawasan, Produktivitas Kerja.